Thioesterase superfamily member 2/acyl-CoA thioesterase 13 (Them2/Acot13) regulates hepatic lipid and glucose metabolism - Kang, Hye Won (Federation of American Societies for Experimental Biology, 2012)
Members of the acyl-CoA thioesterase (Acot) gene family catalyze the hydrolysis of fatty acyl-CoAs, but their biological functions remain unknown. Thioesterase superfamily member 2 (Them2; synonym Acot13) is a broadly expressed mitochondria-associated Acot. Them2 was previously identified as an interacting protein of phosphatidylcholine transfer protein (PC-TP). Pctp(−/−) mice exhibit altered fatty acid metabolism that is accompanied by reduced hepatic glucose production. To examine the role of Them2 in regulating hepatic lipid and glucose homeostasis, we generated Them2(−/−) mice. In livers of Them2(−/−) mice compared with Them2(+/+) controls, a 1.9-fold increase in the K(m) of mitochondrial thioesterase activity was accompanied by a 28% increase in fatty acyl-CoA concentration. A reciprocal 23% decrease in free fatty acid concentration was associated with reduced activation of peroxisome proliferator-activated receptor α. However, fatty acid oxidation rates were preserved in livers of Them2(−/−) mice, suggesting that Them2 functions to limit β-oxidation. Hepatic glucose production was also decreased by 45% in the setting of reduced hepatocyte nuclear factor 4α (HNF4α) expression. When fed a high-fat diet, Them2(−/−) mice were resistant to increases in hepatic glucose production and steatosis. These findings reveal key roles for Them2 in the regulation of hepatic metabolism, which are potentially mediated by PC-TP-Them2 interactions.—Kang, H. W., Niepel, M. W., Han, S., Kawano, Y., Cohen, D. E. Thioesterase superfamily member 2/acyl-CoA thioesterase 13 (Them2/Acot13) regulates hepatic lipid and glucose metabolism.